Red Imported Fire Ant (Solenopsis invicta) Chemosensory Proteins Are Expressed in Tissue, Developmental, and Caste-Specific Patterns - Wanchoo, Arun; Zhang, Wei; Ortiz-Urquiza, Almudena; Boswell, John; Xia, Yuxian; Keyhani, Nemat O. (Frontiers in Physiology, 2020)
The red imported fire ant, Solenopsis invicta, is a eusocial invasive insect that has spread worldwide. Chemosensory proteins (CSPs) are ligand-binding proteins that participate in a diverse range of physiological processes that include olfaction and chemical transport. Here, we performed a systematic survey of the expression of the 21 gene S. invicta CSP family that includes at least two groups of apparent S. invicta-specific gene expansions. These data revealed caste, tissue, and developmental stage-specific differential expression of the SiCSPs. In general, moderate to high SiCSP expression was seen in worker antennae and abdomen tissues with lower expression in head/thorax regions. Male and female alates showed high antennal expression of fewer SiCSPs, with the female alate thorax showing comparatively high SiCSP expression. SiCSP expression was lower in male alates tissues compared to workers and female alates, albeit with some highly expressed SiCSPs. SiCSP expression was low during development including in eggs, larvae (early and late instars), and pupae. Global analyses revealed examples of conserved, divergent, and convergent SiCSP expression patterns linked to phylogenetic relationships. The developmental and caste-specific variation seen in SiCSP expression patterns suggests specific functional diversification of CSPs that may translate into differential chemical recognition and communication among individuals and/or reflect other cellular roles of CSPs. Our results support a model for CSPs acting as general ligand carriers involved in a wide range of physiological processes beyond olfaction. As compared to the expression patterns of the S. invicta odorant binding proteins (OBPs), an inverse correlation between SiOBP and SiCSP expression was seen, suggesting potential complementary and/or compensatory functions between these two classes of ligand carriers.